Agent and Multi-Agent Systems: Technologies and Applications 5th KES International Conference, KES-AMSTA 2011, Manchester, UK, June 29 - July 1, 2011. Proceedings - O'Shea, James; Nguyen, Ngoc Thanh; Crokett, Keeley; Howlett, Robert J.; Jain, Lakhmi C. (Apress, 2011)
This book constitutes the refereed proceedings of the 5th KES International Conference on Agent and Multi-Agent Systems, KES-AMSTA 2011, held in Manchester, UK, in June/July 2011. The 69 revised papers presented were carefully reviewed and selected for inclusion in the book. In addition the volume contains one abstract and one full paper length keynote speech. The papers are organized in topical sections on conversational agents, dialogue systems and text processing; agents and online social networks; robotics and manufacturing; agent optimisation; negotiation and security; multi-agent systems; mining and profiling; agent-based optimization; doctoral track; computer-supported social intelligence for human interaction; digital economy; and intelligent workflow, cloud computing and systems